2010
DOI: 10.3109/09286586.2010.498662
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Biometry to Cataract Outcomes in a Surgical Unit in Africa

Abstract: Biometry in combination with small-incision techniques improves refractive outcomes and decreases undesired postoperative hyperopia. Assuming good surgical skills, better outcomes with biometry justify cataract operation at an earlier stage, thereby reducing intra- and postoperative complications and avoiding years of visual disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 21 publications
5
12
4
Order By: Relevance
“…There is a marked increase in prediction error of biometry in eyes with ocular co-morbidity, and eyes with no ocular comorbidity with pre-operative VA \ 6/60 also increase the prediction error of biometry [27]. In Kenya, it was predicted that use of biometry could improve the proportion of 'good refractive outcomes' (defined as ?1-1.5D spherical equivalent) [8]. In that study, 48.8 % of men and 61.4 % of women had a good refractive outcome with standard 22D lenses without biometry.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…There is a marked increase in prediction error of biometry in eyes with ocular co-morbidity, and eyes with no ocular comorbidity with pre-operative VA \ 6/60 also increase the prediction error of biometry [27]. In Kenya, it was predicted that use of biometry could improve the proportion of 'good refractive outcomes' (defined as ?1-1.5D spherical equivalent) [8]. In that study, 48.8 % of men and 61.4 % of women had a good refractive outcome with standard 22D lenses without biometry.…”
Section: Discussionmentioning
confidence: 95%
“…Encouragingly, less than 2 % of surgeries had a poor visual outcome, and less than 10 % of operations resulted in a borderline outcome following pinhole correction. Although we consider 22D IOL to be the most appropriate power, in another African population, best fit of IOL is considered to be ?21D in men and ?22D in women [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[43] Therefore the challenge is to translate the available technology to benefit the blind and visually impaired poor populations in LMIC, at a pace that can reach the stated goals within the shortest span of time. At the time when professionals are documenting that technology like biometry and manual small incision cataract surgery/phacoemulsification can revolutionize visual outcomes after cataract surgery,[4445] there comes evidence from West Africa on high rates of couching and appalling visual outcomes as a consequence, even to this day. [46]…”
Section: Discussionmentioning
confidence: 99%
“…9 Advances in technology have made biometry more portable and feasible to perform in remote locations. Briesen et al 10 predicted that using biometry in Kenyan cataract camps would increase the number of patients with a spherical equivalent between C1.00 and À1.50 D from 57.3% to 71.1%. In a national survey of Nigeria based on biometry data, Imam et al 11 found that IOL powers of 20.00 D and 21.00 D would be the most suitable for the population.…”
Section: Discussionmentioning
confidence: 98%